A one-way coupled numerical magnetic field and CFD simulation of viscoplastic compressible fluids in MR dampers. (1st February 2020) - Elsaady, Wael; Oyadiji, S. Olutunde; Nasser, Adel
Highlights: A new coupled model for analysis of viscoplastic fluid behaviour is presented. Multi-physics coupled simulation between the fluid flow field and magnetic field. Investigation of internal fluid flow via single- and two-phase CFD simulation. Model includes transient 2-D dynamic flow analysis instead of quasi-static 1-D analysis. Damper hysteresis due to fluid compressibility, inertia, and air existence are predicted. Parametric numerical analysis of the effects of different design parameters on MR dampers. Abstract: Recent developments in employment of magnetorheological (MR) fluids in different applications heighten the need for better understanding of their non-linear flow characteristics. In this paper, the modelling of the dynamic hysteretic behaviour of a twin-tube MR damper via a novel one-way coupled numerical approach is presented. The approach couples the Finite Element Analysis (FEA) of the MR damper magnetic circuit with the Computational Fluid Dynamics (CFD) analysis of the fluid flow field. A User-Defined Function (UDF) predefines the fluid shear-rate-dependent apparent viscosity into the CFD solver according to the magnetic field density attained from the FE solver. Two transient CFD cases are presented, one of them studies the flow in the damper as an incompressible single-phase flow, while the other accounts for the effect of fluid compressibility in the liquid-gas domain as a two-phase flow. The validation of the proposed numerical approaches is achieved via the direct comparison with the published experimental measurements for the same MR damper. It has been found that the fluid compressibility affects the hysteretic behaviour of MR dampers greatly. Moreover, the flow field shows the distributions of pressure, velocity and viscosity contours. In particular, the results show higher non-Newtonian viscosity in the throttling area and lower Newtonian viscosity elsewhere. Furthermore, it is shown that the variation of some design parameters of the damper, such as the width of magnetic poles, input current and frequency of the piston motion, has significant effects on the damper behaviour. Graphical abstract: Image, graphical abstract